2014
DOI: 10.3892/or.2014.3687
|View full text |Cite
|
Sign up to set email alerts
|

miR-142 acts as a tumor suppressor in osteosarcoma cell lines by targeting Rac1

Abstract: Abstract. Although the 5-year survival rate of osteosarcoma (OS) has risen to ~60-70%, a substantial portion of patients still respond poorly to chemotherapy and have a high risk of relapse or metastasis even after curative resection. In this study, we found that the expression of miR-142 was significantly reduced in OS tissues and OS cell lines, while Ras-related C3 botulinum toxin substrate 1 (Rac1) expression was increased in the OS tissues and OS cell lines compared with expression in the controls. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 26 publications
(27 reference statements)
3
50
1
Order By: Relevance
“…In this work, the overexpression of SRGAP2 also slowed cellular migration in murine osteosarcoma cell lines and the knockout of Srgap2 increased cellular migration in the K12 cell line. However, unlike what has been observed in other studies of SRGAP2, knockout of Srgap2 slowed cellular proliferation in osteosarcoma cell lines1624.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…In this work, the overexpression of SRGAP2 also slowed cellular migration in murine osteosarcoma cell lines and the knockout of Srgap2 increased cellular migration in the K12 cell line. However, unlike what has been observed in other studies of SRGAP2, knockout of Srgap2 slowed cellular proliferation in osteosarcoma cell lines1624.…”
Section: Discussioncontrasting
confidence: 93%
“…Other modulators of Rac1 have also been implicated in osteosarcoma metastasis. Micro-RNA (miR)-142 has been shown to regulate Rac1 expression in osteosarcoma cell lines by targeting the 3’-untranslated region of the SRGAP2 transcript and blocking translation of the protein24. Expression of miR-142 or direct silencing of Rac1 inhibited cellular invasion as well as cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is a GTPase that is involved in diverse physiological activities, including cell growth, migration and invasion [33]. Until now, large numbers of miRNAs are reported to act as tumor suppressors by targeting Rac1, including miR-142 and miR-146a [34, 35]. Previous studies also proved that Rac1 participates in various cardiovascular pathologies, for example, cardiomyocyte hypertrophy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that LDHA downregulation inhibits cell migration, invasion and tube formation. Furthermore, our data showed that depletion of LDHA decreased the expression of MMP-2 and MMP-9, suggesting that LDHA may be involved in RCC invasion through inducing enzyme-based degradation of the extracellular matrix [23,24] . Furthermore, it is worth noting that LDHA depletion with siRNA leads to diminished VEGF and VE-cadherin levels, which are known to modulate vascular angiogenesis [25] and tumor development [26,27] .…”
Section: Discussionmentioning
confidence: 86%